VERIFIKASI PARAMETER PENGUJIAN SURFAKTAN ANIONIK DALAM AIR LIMBAH DENGAN METODE MBAS MENGGUNAKAN SPEKTROFOTOMETER UV-VIS - Victoria, Stefanie; Sitorus, Saibun; Panggabean, Aman Sentosa (Jurusan Kimia FMIPA UNMUL, 2022)
Determination of the parameters verification of anionic surfactants in waste water samples based on the MBAS (Methylene Blue Active Substances) method using a UV-Vis spectrophotometer has been done. Verification of the measurement parameters refer to SNI 06-6989.51- 2005. The measurement results of several verification parameters is good showed that the linearity of the measurement indicated by the correlation coefficient value of 0.9909. The detection limit and quantitation limit values ​​obtained were 0.3622 mg/L and 1.2072 mg/L respectively. The precision value with %RSD was 2.5415%, and the %RPD value was 3.0686%. It is stated that this method can be used for the analysis of anionik surfactants in laundry wastewater and can be applied as a routine test at PT. Global Environment Laboratory.